PROTOTIPE MONITORING PENYIMPANAN GABAH BERBASIS INTERNET OF THINGS (IOT) - Pratama, Wahyu Adi; Nurchim, Nurchim; Pamekas, Bondan Wahyu (Infotech: Journal of Technology Information, 2024)
This study aims to develop and implement a prototype for monitoring temperature and humidity in rice storage facilities based on the Internet of Things (IoT), focusing on monitoring the environmental conditions of the storage area and the rice itself. The system conducts real-time monitoring of temperature, room humidity, and rice humidity. This prototype is equipped with humidity sensors that are directly installed inside the rice stacks within the sacks to monitor the condition of the rice directly. Data collected by the sensors will be sent to an ESP32 microcontroller for analysis and displayed via an LCD or a website. Thus, this research contributes to the development of advanced technology to improve the quality and efficiency of rice storage in the agricultural context, as well as to strengthen the application of IoT in the fields of agriculture and Informatics Engineering. The results of this study are expected to help farmers and storage managers maintain rice quality, reduce losses due to suboptimal storage conditions, and provide insights for better storage management. ABSTRAKPenelitian ini bertujuan untuk mengembangkan dan menerapkan prototipe pemantauan suhu dan kelembapan pada tempat penyimpanan gabah berbasis Internet of Things (IoT) yang fokus pada monitoring kondisi lingkungan penyimpanan dan gabah itu sendiri. Sistem melakukan pemantauan secara real-time terhadap suhu, kelembapan ruangan, dan kelembapan gabah. Prototipe ini dilengkapi dengan sensor kelembapan yang dipasang langsung di dalam tumpukan gabah pada karung untuk memonitor kondisi gabah secara langsung. Data yang dikumpulkan oleh sensor akan dikirimkan ke mikrokontroller esp32 untuk dianalisis dan ditampilkan melalui LCD maupun website. Dengan demikian, penelitian ini memberikan kontribusi dalam pengembangan teknologi canggih untuk meningkatkan kualitas dan efisiensi penyimpanan gabah dalam konteks pertanian, serta memperkuat aplikasi IoT dalam bidang pertanian dan teknik informatika. Hasil dari penelitian ini diharapkan dapat membantu petani dan pengelola tempat penyimpanan dalam menjaga kualitas gabah, mengurangi kerugian akibat kondisi penyimpanan yang tidak optimal, dan memberikan wawasan untuk pengelolaan penyimpanan yang lebih baik.